Pengaruh Jarak Tanam Dan Dosis Pupuk Organik Terhadap Pertumbuhan Dan Hasil Kacang Tanah (Arachis Hypogaea L.) Di Lahan Kering - Enjel Kristiani Zalukhu; Benediktus Buala’aro Giawa; Fedilina Tafonao; Kristiani Telaumbanua; Nelceria Halawa; Yoel Melsaro Larosa; Putra Hidayat Telaumbanua (CV. SINAR HOWUHOWU, 2025)
A legume crop with strategic importance in meeting national food needs, groundnuts (Arachis hypogaea L.) have the ability to be grown in arid regions. However, boosting this crop's output is hampered by low rainfall and soil fertility. This study uses a literature review technique to scientific journals for the 2021–2025 period in order to determine the impact of planting distance and organic fertilizer dosage on peanut development and yield in drylands. The analysis's findings demonstrate that ideal spacing, like 40 cm by 20 cm or 30 cm by 15 cm, can greatly boost peanut seed output and vegetative growth. Meanwhile, the application of organic fertilizers such as manure and biochar is proven to improve soil physical and chemical properties, increase water retention, and support nutrient absorption by plants. The synergy between proper spacing and organic fertilizer application can increase yields by more than 30%, and support sustainable cultivation systems on marginal land.